Hepatobiliary Events in Migraine Therapy with Herbs—The Case of Petadolex, A Petasites Hybridus Extract - Anderson, Nora (J Clin Med, 2019)
Petadolex(®), a defined butterbur extract has clinically proven efficacy against migraine attacks. However, spontaneous reports indicate cases of herbal induced liver injury (HILI). While most HILI patients presented mild serum biochemistry changes (<3 ULN, dose range 50 to 225 mg/day; treatment duration 4–730 days) nine developed severe HILI (average time-to-onset 103 days, ALT-range 3–153; AST 2–104-fold ULN). HILI cases resolved after medication withdrawal though two patients required liver transplantation. Liver biopsies revealed an inconsistent injury pattern, i.e. necrosis, macrovesicular steatosis, inflammation, cholestasis, and bile duct proliferation. Causality assessment rated 3 cases likely, 13 possible, 8 unlikely and 24 as unclassifiable/unclassified. Note, 22 patients reported hepatotoxic co-medications especially during periods of pain. A no-observable-adverse-effect-level at 15-fold of the maximal clinical dose (3 mg/kg/day MCD) was established for rats. At >45 and 90-fold MCD bile duct hyperplasia was observed but could not be confirmed in an explorative minipig study at 218-fold MCD. Human hepatocyte studies at 49-fold C(max) serum petasins (=active ingredient) and therapeutic Ibuprofen, Paracetamol and Naratriptan concentrations evidenced liver transaminase and CYP-monooxygenase changes. Collectively, Petadolex(®) HILI cases are rare, idiosyncratic and frequently confounded by co-medications. A physician-supervised self-medication plan with herbs and pain relief medication is needed to minimize risk for HILI.